Socialization and Implementation of Compost Bin Technology as an Environmentally Friendly Solution in Elementary Schools: English - Wayan Sri Maitri; Komang Widhya Sedana Putra P; Ni Wayan Lasmi (Paramacitra Jurnal Pengabdian Masyarakat, 2026)
Environmental problems related to organic waste management remain a major challenge in many elementary schools. Limited knowledge, inadequate facilities, and the lack of practical environmental education often result in improper waste disposal practices. This condition reduces students’ awareness of environmental sustainability and limits their involvement in waste management activities. Therefore, effective and applicable solutions are required to strengthen environmental education at an early age. This community service program aimed to improve students’ environmental literacy and practical skills through the socialization and implementation of compost bin technology at SD Desa Padangsambian Klod, Denpasar. The program was conducted on February 6, 2026, using a participatory approach that combined socialization sessions, practical demonstrations, guided practice, and continuous mentoring. The preparation stage included preliminary observation, coordination with school authorities, and the development of learning materials. During the implementation stage, students were introduced to waste sorting concepts and trained to process organic waste using compost bins. The reflection and evaluation stage was carried out through observation, discussions, and feedback from participants. The results showed significant improvements in students’ understanding and behavior regarding organic waste management. After participating in the program, students were able to distinguish between organic and inorganic waste, actively use compost bins, and demonstrate greater responsibility in maintaining a clean school environment. Student participation increased noticeably, and teachers became more involved in supervising and integrating composting activities into daily learning routines. These changes indicate that hands-on learning supported by simple technology can effectively enhance environmental awareness and sustainable practices among students. In conclusion, the implementation of compost bin technology serves as an effective educational tool for promoting environmentally responsible behavior in elementary schools. The program successfully achieved its objectives of increasing environmental literacy, strengthening practical skills, and fostering sustainable habits. Future community service programs are encouraged to expand environmental education initiatives to strengthen long-term environmental sustainability.